Kandungan Mikroplastik Pada Garam di Pasar Terong Kelurahan Bontoala Kota Makassar - Muhammad Ikrar Tri Murpa; Alfina Baharuddin; Abdul Gafur (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2021)
Salt is a white, crystalline solid which is a collection of compounds with the largest portion of Sodium Chloride (more than 8%) and other compounds such as Magnesium Chloride, Magnesium Sulfate, Calcium Chlorida, and others. Salt has properties or characteristics which means it is easy to absorb water, bulkdensity (density level) of 0.8 to 0.9 and melting point at a temperature level of 801°C. To determine the microplastic content of salt in the Terong Market, Bontoala Village, Makasaar City in 2019. This type of research is an observational study with a descriptive approach. The results of this study indicate that all salt samples examined at the Marine Ecotoxicology Laboratory, Department of Marine Sciences, Faculty of Marine Sciences and Fisheries, Hasanuddin University, Makassar 100% contain microplastics. The author suggests to the public to pay more attention to the environmental cleanliness of the eggplant market in order to avoid the effects of environmental pollution and reduce the use of excessive plastic. Keywords: Salt, Microplastic, Traditional Market